Gut Antibiotic Inactivation by Β-Lactamases Is Intended to Prevent Microbiome Damage and Attenuate Antibiotic Resistance in Large Animal Models. (4th October 2017) - Connelly, Sheila; Furlan-Freguia, Christian; Subramanian, Poorani; Hasan, Nur A; Colwell, Rita R; Kaleko, Michael
Abstract: Background: Exposure of the gut microbiome to antibiotics can harm the microbiota and lead to antibiotic resistance. SYN-004 (ribaxamase) is a clinical-stage, oral β-lactamase enzyme intended to preserve the gut microbiome by inactivating certain IV β-lactam antibiotics in the GI tract without affecting antibiotic infection control efficacy. The use of ribaxamase for microbiome protection from both IV and orally-delivered antibiotics was explored using two large animal models of antibiotic-mediated gut dysbiosis. Methods: Ribaxamase was manufactured as enteric-coated pellets for pH-mediated release in the upper GI tract. New formulations, named SYN-007, were engineered to be released in the GI tract at a point distal to oral antibiotic absorption. Ribaxamase and SYN-007 were evaluated in a pig model of antibiotic-mediated microbiome disruption, and SYN-007 was evaluated in dogs. Pigs were treated with ceftriaxone (CRO; IV, 50 mg/kg, SID) or amoxicillin (AMX; PO, 20 mg/kg, BID) for 7 days +/- ribaxamase (PO, 75 mg, QID). Dogs received AMX (80 mg/kg, PO) +/- SYN-007 (10 mg, PO). Serum antibiotic levels were measured via HPLC or LC/MS, and fecal DNA whole genome shotgun (WGS) sequence analyses were performed. Results: In pigs, ribaxamase protected the gut microbiome from IV CRO and oral AMX and reduced propagation of antibiotic resistance genes. Ribaxamase had no effect on CRO serum levels. In contrast, AMX was not detected in the serum when delivered with ribaxamase indicating that AMX was degraded in the GI tract prior to its absorption. Delivery of delayed-release SYN-007 with oral AMX in dogs did not affect AMX absorption, as AMX serum pharmacokinetics (PK) was similar with and without SYN-007. Conclusion: Ribaxamase protected the gut microflora in pigs from damage caused by IV CRO and reduced the emergence of antibiotic resistance genes. SYN-007, a novel formulation designed to target enzyme release distal to the site of AMX absorption, did not affect AMX serum levels in dogs, indicating that the β-lactamase was not released prior to AMX absorption. SYN-007 has the potential to expand microbiome protection via antibiotic inactivation to include oral as well as IV β-lactam antibiotics. Disclosures: S. Connelly, Synthetic Biologics, Inc.: Employee, Salary. C. Furlan-Freguia, Synthetic Biologics, Inc.: Employee and Shareholder, Salary and Stock Options. P. Subramanian, CosmosID, Inc.: Employee, Salary. N. A. Hasan, CosmosID, Inc.: Employee, Salary. R. R. Colwell, CosmosID, Inc.: Employee, Salary. M. Kaleko, Synthetic Biologics, Inc.: Employee and Shareholder, Salary and stock options